ANALISIS PENYELESAIAN UTANG PIUTANG PADA LAYANAN FINTECH LENDING MELALUI KEPAILITAN & PKPU - Ahmad Fachri Faqi; Fadilla Jamila (Jurnal Privat Law, 2024)
Debt settlement in Fintech Lending services has been regulated under POJK 10/2022. In addition to dispute resolution through the district court or alternative dispute resolution, there are Bankruptcy and PKPU mechanisms to resolve debt issues in Fintech Lending services.. This research analyzes the settlement of debts in Fintech Lending services through Bankruptcy and Suspension of Debt Payment or PKPU institutions as a fairer, faster, and more effective alternative. The research method used is normative legal research using secondary data such as laws and regulations and related legal literature. Data collection techniques are carried out through documentation studies or literature studies. The results showed that debt settlement in Fintech Lending services can be done through Bankruptcy and PKPU, because the debt is included in the scope of Law 37/2004. However, there are obstacles in the application of debt collection principles in Law 37/2004, such as the requirement of advocates and the number of creditors that make it difficult for individual debtors. In addition, Law 37/2004 has not fully protected individual debtors because debt relief still requires creditor approval.